PERLATIHAN MANAJEMEN RESIKO BAGI KOPERASI SIMPAN PINJAM/UNIT SIMPAN PINJAM DI KOTA SURAKARTA - Paulus Wardoyo; Endang Rusdianti (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2018)
Cooperatives are one of the pillars of the Indonesian economy aimed at promoting the welfare of members and society. The dominant forms of cooperatives in Surakarta City are the Savings and Loans cooperative (KSP) and the Savings and Loans Unit (USP) whose activities are similar to Rural Banks, but in practice it turns out that they lack the precautionary principle and risk management. The scope of KSP / USP is very limited because it can only accept deposits or provide loans to members / prospective members. The implementation of this service is in the form of risk management training so that KSP / USP management can increase knowledge about the importance of the precautionary principle in its management. Implementation method of service through training for 2 (two) days in collaboration with the PPUPIK-PPKU Semarang University and the Surakarta City Cooperatives & SMEs Office. The result of dedication is the increase in understanding and ability of the management in managing the risk of deposit and lending activities, for example in calculating and converting interest rates, as well as in establishing reserves for uncollectible loans, analyzing and binding credit agreements.